THE METHOD OF USING COOPERATIVE TEACHING TECHNOLOGY IN THE DEVELOPMENT OF STUDENT’S BIOLOGICAL COMPETENCIES BASED ON A SYNERGISTIC APPROACH - Sharipova Dildora Rajabovna (Next Scientists Conferences, 2023)
The article describes the method of using collaborative learning technology in the development of biological competencies of students based on a synergistic approach to teaching biology.